Digitalisasi Usaha Mikro Kecil dan Menengah (UMKM) bagi Peserta Sekolah Perempuan Capai Impian dan Cita-Cita (Sekoper Cinta) Jawa Barat: Digitalization of Micro, Small and Medium Enterprises (MSMEs) for Sekolah Perempuan Capai Impian dan Cita-Cita (Sekoper Cinta) West Java - Narimawati, Umi; Mauluddin, Syahrul; Winanti, Marliana Budhiningtias; Pangaribuan, Imelda; Rahmatya, Myrna Dwi; Sidik, Rangga; Fadillah, Annisa Paramitha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This Community Service aims to digitize women's Micro, Small, and Medium Enterprises (MSMEs) in Sekoper Cinta (Sekolah Perempuan Capai Impian dan Cita-Cita) West Java. Sekoper Cinta is a non-formal school that exists to carry out special empowerment for women, one of which is through a vocational training program in e-commerce. However, only a small proportion of them can obtain it, while the participants in the Sekoper Cinta program in West Java totaled 34,900 women. Therefore, through this Community Service program, we aim to empower women. The stages of Community Service are preparation, initial evaluation, vocational training in e-commerce, mentoring, and final evaluation. The result achieved from this Community Service is an increase in the skills of participants in selling in online stores and on social media.